Production of charmed baryons in p¯p collisions close to their thresholds - Haidenbauer, J. (2017)
Cross sections for the charm-production reactions p-p→Λ-c-Σc+, Σ-cΣc, Ξ-cΞc, and Ξ-c′Ξc′ are presented, for energies near their respective thresholds. The results are based on a calculation performed in the meson-exchange framework in close analogy to earlier studies of the Jülich group on the strangeness-production reactions p-p→Λ-Σ, Σ-Σ, Ξ-Ξ by connecting the two sectors via SU(4) flavor symmetry. The cross sections are found to be in the order of 0.1-1 μb at energies of 100 MeV above the respective thresholds, for all considered channels. Complementary to meson exchange, where the charmed baryons are produced by the exchange of D and D∗ mesons, a charm-production potential derived in a quark model is employed for assessing uncertainties. The cross sections predicted within that picture turn out to be significantly smaller.